The 18th Dynasty banquet: ideals and realities - Harrington, N (2010)
Mortuary (as opposed to funerary) banquet scenes were commonly depicted on the walls of Egyptian tombs of the Eighteenth Dynasty. They show the tomb-owner and his wife before a table of offerings in the company of family and friends; the presence of musicians and servants differentiates this particular scene style from other depictions of offering found in these and in later New Kingdom paintings. Banqueting in the presence of the dead was part of elite cultic activity centred on the ancestors, which took place at Thebes and possibly other sites including Memphis and Elkab. Whether poorer social classes took part in comparable feasting is not clear from textual or archaeological sources, although there are indications that non-elites may have had some form of mortuary cult as evidenced at the Amarna South Tombs Cemetery. In this paper, the ideals presented in banquet scenes will be discussed along with evidence for feasting in the vicinity of tombs, with particular reference to Deir el-Medina and the Theban necropolis. Much research has been published on the paintings themselves, particularly by Lise Manniche who emphasizes their sexual aspects. However, the scenes not only reflect the concern for rebirth suggested by sensual imagery, but, perhaps more importantly, the part the relatives and friends of the deceased were expected to play in the maintenance of the tomb-owner's cult.